(Invited) The Use of Silicon-Germanium Superlattices in Thermoelectric Devices and Microfabricated Generators. (18th August 2016) - Ferre Llin, Lourdes; Mirando, Francesco; Samarelli, Antonio; Odia, Ameze; Cecchi, Stefano; Etzelstorfer, Tanja; Müller Gubler, Elisabeth; Chrastina, Daniel; Isella, Giovanni; Stangl, Julian; Weaver, John M R; Dobson, Phil; et al.
Abstract : Low dimensional structures such as superlattices have the potential to improve the thermoelectric properties of materials by engineering the scattering of phonons to reduce the thermal conductivity and therefore improve the thermeoelectric performance. Here we demonstrate the reduction in thermal conductivity in Ge/SiGe superlattices using multiple barrier engineering to scatter acoustic phonons at the key wavelengths for thermal transport. The approach allows ZT to be increased in wide quantum well superlattices through the reduction of heterointerfaces which scatter both electrons and phonons.